Новые технические решения для совершенствования подготовительных работ на лесозаготовках - Gornostaev V. N. (A breakthrough in science: development strategies, 2017)
new technical solutions for improving the preparatory work at logging sites, patented by specialists of Petrozavodsk University, are presented.
Keywords: лесозаготовки; патент; подготовительные работы; logging; preparatory work; patent